1993
DOI: 10.1042/bj2890875
|View full text |Cite
|
Sign up to set email alerts
|

Diacylglycerol kinase is phosphorylated in vivo upon stimulation of the epidermal growth factor receptor and serine/threonine kinases, including protein kinase C-ε

Abstract: In signal transduction, diacylglycerol (DG) kinase attenuates levels of the second messenger DG by converting it to phosphatidic acid. A previously cloned full-length human 86 kDa DG kinase cDNA was expressed as fusion protein in Escherichia coli, to aid in the generation of DG-kinase-specific monoclonal antibodies suitable for immunoprecipitation experiments. To investigate whether phosphorylation of DG kinase is a possible mechanism for its regulation, COS-7 cells were transiently transfected with the DG kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 42 publications
2
62
0
Order By: Relevance
“…MKP5 was subcloned into pMT-SM III, a modi®ed version of the eukaryotic expression vector pMT-SM (Muda et al, 1996a;Schaap et al, 1993), in which the 9E10 Myc epitope coding sequence is incorporated, in-frame, into the multiple cloning site. Primers TTAGGTACCTGT-CTTGAGTTCTT-CTTGAATTGC (nucleotides 74 ± 106) and CCATCTAGA-CCACGCCCATCAGC (nucleotides 1579 ± 1545) were used to amplify MKP5 ORF from human breast cDNA (the underlined nucleotides correspond to the engineered Asp718 and XbaI sites).…”
Section: Mammalian Expression Plasmidsmentioning
confidence: 99%
“…MKP5 was subcloned into pMT-SM III, a modi®ed version of the eukaryotic expression vector pMT-SM (Muda et al, 1996a;Schaap et al, 1993), in which the 9E10 Myc epitope coding sequence is incorporated, in-frame, into the multiple cloning site. Primers TTAGGTACCTGT-CTTGAGTTCTT-CTTGAATTGC (nucleotides 74 ± 106) and CCATCTAGA-CCACGCCCATCAGC (nucleotides 1579 ± 1545) were used to amplify MKP5 ORF from human breast cDNA (the underlined nucleotides correspond to the engineered Asp718 and XbaI sites).…”
Section: Mammalian Expression Plasmidsmentioning
confidence: 99%
“…Dominant negative Grb2 (∆NGrb2), in which the N-terminal SH3 domain is deleted, was from A. M. Pendergast (Duke University) [35]. Dominant negative p74 Raf-" , (N∆Raf) which only contains the Nterminal regulatory domain of Raf-1 (residues 1-258) [36], inactive p110 (p110∆kin) with a mutated inactive ATP site [37], and constitutively activated p110 (p110*) in which the p85 inter-SH2 domain was ligated to the amino terminus of p110, were from Dr. L. T. Williams (San Francisco) [38]. A dominant negative mutant of p85 (∆p85) which lacks a p110 binding site (residues 479-513) was from Dr. M. Sakaue [39].…”
Section: Dna Constructsmentioning
confidence: 99%
“…This may be explained by the report that the 80 kDa DAG kinase translocates to the membrane [16,23,26] or cytoskeleton of cells [8], in response to epidermal growth factor stimulation [26]. It has also been shown that protein kinase C isoforms phosphorylate DAG kinase in itro [26,27].…”
Section: Introductionmentioning
confidence: 98%